Environmental regulation and technology transfers - Takao Asano; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2012)
This paper analyzes the situation in which a national government introduces environmental regulations. Within the framework of an international duopoly with environmental regulations, this paper shows that an environmental tax imposed by the government in the home country can induce a foreign firm with advanced abatement technology to license it to a domestic firm without this technology. Furthermore, when the domestic firm's production technology is less efficient than that of the foreign firm, the foreign firm may freely reveal its technology to the domestic firm. These improvements through the voluntary transfer of technology support the Porter hypothesis, which states that environmental regulations have positive impacts on innovation.
Keywords: Q56; F18; H23; L13; 330; Environmental regulation; Technology transfer; International competition; Duopoly; Internationale Umweltpolitik; Technologietransfer; Internationaler Wettbewerb; Duopol; Theorie